PENGARUH PERBEDAAN PERLAKUAN PENDAHULUAN TERHADAP RENDEMEN MINYAK ATSIRI DAUN JERUK PURUT - Febrina, Dina (Viva Medika, 2019)
Indonesia and Asian countries use kaffir lime (Citrus hystrix DC) as a natural fragrance ingredient in various food and beverage products. In addition to flavoring food, kaffir lime by the community have long been known as traditional medicine. Cytronel is a chemical compound that has kaffir lime which is 81.49%. In addition to citronelal it was reported that linalool, cytronelyl-acetate, citronellol and geraniol were identified in kaffir lime. Although extraction of kaffir lime has not been done much, essential oils of kaffir lime are one of the potential alternatives in the food, beverage and perfume industry. The difference in yields of the treatment of drying and using ripening of fresh leaves is done to give an overview of the extraction of the best essential oils from kaffir lime leaves. The difference in the treatment of simplicia carried out before distillation showed better yields, namely the ripening treatment with yield of ± 0.80179%.